Аналіз медико-демографічних процесів у Запорізькій області протягом 2015-2021 років - Федорченко, Руслана Анатоліївна; Тищенко, Т. М.; Куцак, Алла Валеріївна; Fedorchenko, R. A.; Tyshchenko, T. M.; Kutsak, A. V. (My University, 2025)
Мета: дослідити медико-демографічні процеси в Запорізькій області протягом 2015–2021 років, проаналізувати структуру смертності та показники смертності населення за основними причинами смерті, провести порівняльний аналіз із доковідним періодом і з іншими регіонами України. Матеріали та методи. Базою є матеріали Державної служби статистики України та Головного управління статистики Запорізької області за 2015–2021 роки. У роботі використані ретроспективний аналіз, медико-статистичний і системний аналіз, а також методи логічного узагальнення. Результати. Коефіцієнт природного приросту населення в Запорізькій області у 2021 році знизився на 39,2%. Рівні серед міського та сільського населення істотно не відрізнялись. Загальний коефіцієнт смертності протягом 2015–2019 рр. був високим, у 2021 р. досягнув максимального значення – 21,6/1 000 нас. Значення коефіцієнтів смертності були вищими в сільській місцевості, але темпи зростання серед міського населення були вдвічі швидшими. Порівняно з українськими показниками зафіксовано односпрямовані тенденції щодо перевищення значень показників у сільській місцевості, але темпи зростання в Запорізькій області випереджали загальноукраїнські майже на 10% як у міських, так і в сільських поселеннях. Середня очікувана тривалість життя у 2021 році становила 68,64 року, але в жінок майже на 10 років є більшою, ніж у чоловіків. Проте чітко відстежується негативна тенденція щодо скорочення тривалості життя майже на 3 роки як серед чоловіків, так і серед жінок. Purpose: to study medical and demographic processes in Zaporizhia region during 2015–2021, to analyze the structure of mortality and mortality rates of the population by main causes of death, to conduct a comparative analysis with the pre-COVID period and with other regions of Ukraine. Materials and methods. The research is based on data materials from the State Statistics Service of Ukraine and the Main Department of Statistics of Zaporizhia region for 2015–2021. To assess medical and demographic processes in Zaporizhia region, the following indicators were selected, calculated and analyzed: birth rate, total mortality rate, natural increase/decrease, mortality of children under one year of age, mortality of the population from certain causes depending on gender, age, place of residence (urban and rural areas), average life expectancy. The work uses retrospective analysis, medical and statistical and system analysis, as well as methods of logical generalization. Results. The natural population growth rate in Zaporizhia region in 2021 decreased by 39,2%. The levels among urban and rural areas did not differ significantly. The overall mortality rate during 2015–2019 was high and in 2021 reached a maximum value of 21,6/1 000 people. The values of mortality rates were higher in rural areas, but the growth rates among the urban population were twice as fast. Compared with Ukrainian indicators, unidirectional trends were recorded in terms of exceeding the values of indicators in rural areas, but the growth rates themselves in Zaporizhzhia region were ahead of the all-Ukrainian ones by almost 10% in both urban and rural settlements. The average life expectancy in 2021 is 68,64 years, but for women it is almost 10 years longer than for men. However, a negative trend is clearly observed in terms of reducing life expectancy among both men and women by almost 3 years. In general, in Zaporizhia region, fertility rates (7.56 ± 1.01; 6.95 ± 0.87; 7.87 ± 0.93/1,000 population) were significantly lower than the all-Ukrainian rates (8.9 ± 0.95; 8.64 ± 0.95; 9.44 ± 0.94/1,000 population), which were registered in urban and rural settlements (t = 3.5, t = 3.1, t = 3.8, p ≤ 0.05). In 2020, on the eve of the tangible consequences of the acute respiratory disease COVID-19, caused by the SARS-CoV-2 coronavirus, the total fertility rate was 1.22 per woman compared to 1.53 in 2012, which is almost half the replacement rate 2.2. The total fertility rate in 2021 was even lower, at 1.16 per woman. According to the Institute of Demography and Quality of Life Problems of the National Academy of Sciences, in 2021 the number of children born was half the number of people who turned 60. The extremely low fertility rate leads to a deformation of the age structure of the population. In particular, during the period of Ukraine's independence, the share of the population aged 65 and older increased from 12% in 1991 to to almost 18% in 2021. According to forecasts, the aging of the population in the country will continue to progress.
Analysis of medical and demographic processes in Zaporizhzhia region during 2015–2021
Keywords: народжуваність; смертність; природний приріст; середня очікувана тривалість життя; смертність дітей віком до одного року; СОVID-19; birth rate; mortality; natural increase; average life expectancy; mortality of children under one year of age